Problematic of the Environmental Education in Educational Institutions - Liliana Hayde Gutierrez Sabogal (Revista Científica, 2016)
The following article sketches the understanding of the actual situation of environmental education in Colombian educational institutions, taking in to account the aspects that seem to have an impact on this problematic and the possible interrelationships between them like the first stage of the doctoral research lead by Doctor Francisco González.